Nausea Transformer - Branco, C.; Dias, J.; Diniz, N. (Proceedings of SIGGRAPH 2007, 2007)
The word "noise" comes from the Latin word nausea, meaning "seasickness", or from a derivative (perhaps Latin noxia) of Latin noceo = "I do harm", referring initially to nuisance noise. Generally, all non-musical sounds are considered to be noise. Noise is a complex concept and source material; it is an invisible architectural element with undefined aesthetics. It profoundly affects people, and yet people feel very powerless to interact with or control it. The fundamental idea is to turn noise into a reprocessed living, evolving and tangible experience by interacting spatially and temporally with the environment and its observers. We aim to raise people's awareness to sound in all its forms: speech, non-speech sound (sound pollution sources) or natural sound, and treat it like data with a corporeal dimension. We aspire to convey an embodiment of an often neglected "hidden dimension", by adding it to a phenomenology and a poetics of visual space. Building up on our research in interactive membranes [1] [2], we introduce "Nausea Transformer": a sound reprocessed machine that unexpectedly can create pleasant behaviours by recycling noise into pleasant sound, therefore promoting new interactive experiences to a nearby audience.